Disordered, Large Interlayer Spacing, and Oxygen‐Rich Carbon Nanosheets for Potassium Ion Hybrid Capacitor. Issue 19 (12th March 2019) - Chen, Jiangtao; Yang, Bingjun; Hou, Hongjun; Li, Hongxia; Liu, Li; Zhang, Li; Yan, Xingbin
Abstract: Potassium ion storage technology as a promising substitute for the well‐developed lithium ion storage technology is still at the infancy stage of development, and exploring suitable electrode materials is critical for its practical application. Here, the great feasibility of disordered, large interlayer spacing, and oxygen‐rich carbon nanosheets (CNSs) prepared by chemical vapor deposition for potassium ion storage applications is demonstrated. As an anode material, the CNSs exhibit outstanding rate capability as well as excellent cyclic stability. Taking advantage of this, a potassium ion hybrid capacitor (PIHC) is constructed by employing such CNSs as the battery‐type anode and activated carbon as the capacitor‐type cathode. The resulting device displays a high energy density of 149 Wh kg −1, an ultrahigh power output of 21 kW kg −1, as well as a long cycling life (80% capacity retention after 5000 cycles), which are all close to the state‐of‐the‐art values for PIHCs. This work promotes the development of high‐performance anode material for potassium ion storage devices, and the designed PIHC pushes the energy density and power density to a higher level. Abstract : Employing Na2 CO3 as template, disordered, large interlayer spacing, and oxygen‐rich carbon nanosheets (CNSs) are prepared by chemical vapor deposition. Such CNS anodes exhibit superior performance for potassium ion storage, and thus the resulting potassium ion hybrid capacitor displays a good overall performance, high energy density, high power density as well as long cycling life.